Designing a Remote Supervisory Operation Interface for Autonomous Urban Passenger Ferries - Yang, Pengrui (My University, 2026)
This thesis explores the design of a Remote Operation Centre interface for super vising autonomous passenger ferries in Gothenburg. It argues that remote ferry op eration is not continuous remote driving, but supervisory work based on mediated information, communication, and bounded intervention. Using a Research through Design approach, the project combined literature review, expert and stakeholder input, scenario reasoning, and iterative prototyping. The final outcome is a high fidelity multi-screen ROC interface. The left screen supports fleet-level monitoring and priority recognition. The right screen supports selected-event diagnosis, com munication, automation recommendation review, and supervisory response. The 24-inch vessel screens provide read-only awareness of individual vessels. The thesis contributes an interface-level design proposal for organising monitoring, communi cation, and supervisory command in autonomous urban ferry operation. The pro totype is not a validated operational system. However, a formative internal review with two Cstrider participants indicated that the overall interface logic was under standable, while also identifying areas for refinement. The prototype can therefore serve as an evaluation-informed foundation for future expert review, simulator-based testing, and ROC interface development.
Keywords: Remote Operation Centre; Autonomous ferrie; maritime HMI; supervisory control; situation awareness; interaction design